Intracellular Ca2+ Concentration and Phosphatidylserine Exposure in Healthy Human Erythrocytes in Dependence on in vivo Cell Age - Bernhardt, Ingolf; Nguyen, Duc Bach; Wesseling, Mauro C.; Kaestner, Lars (Frontiers in Physiology, 2020)
After about 120 days of circulation in the blood stream, erythrocytes are cleared by macrophages in the spleen and the liver. The 'eat me' signal of this event is thought to be the translocation of phosphatidylserine from the inner to the outer membrane leaflet due to activation of the scramblase, while the flippase is inactivated. Both processes are triggered by an increased intracellular Ca2+ concentration. Although, this is not the only mechanism involved in erythrocyte clearance, in this minireview we focus on the following questions: Is the intracellular free Ca2+ concentration and hence phosphatidylserine exposure dependent on the erythrocyte age, i.e. is the Ca2+ concentration progressively raising during the erythrocyte aging in vivo? Can putative differences in intracellular Ca2+ and exposure of phosphatidylserine to the outer membrane leaflet be measured in age separated cell populations? Literature research revealed less than dozen of such publications with vastly contradicting results for the Ca2+ concentrations but consistency for a lack of change for the phosphatidylserine exposure. Additionally we performed reanalysis of published data resulting in an ostensive illustration of the situation described above. Relating these results to erythrocyte physiology and biochemistry we can conclude that the variation of the intracellular free Ca2+ concentration is limited with 10 µM as the upper level of the concentration. Furthermore we propose the hypothesis that variations in measured Ca2+ concentrations may to a large extend depend on the experimental conditions applied but reflect a putatively changed Ca2+ susceptibility of erythrocytes in dependence of in vivo cell age.